The Routledge handbook of gender and violence - Lombard, Nancy (Routledge, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Documenter le processus de déploiement d'une communauté virtuelle de pratique (CVP): le cas de la CVP de la CLES - Reynolds, Jeanne; Thoër, Christine (Service aux collectivités de l'UQAM, 2018)
Recherche réalisée en partenariat avec la Concertation des luttes contre l'exploitation sexuelle (CLES)
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; approches et analyses; exploitation sexuelle; femmes*; industrie du sexe; outils; prévention; périodes historiques; rapports sociaux de sexe; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; thématiques; violences; violences contre les femmes*